The Cosmic Breath Spirit and Nature in the Christianity-Buddhism-Science Trialogue. - Yong, Amos. (Leiden : BRILL, 2012)
The interjection of pneumatology in both theologies of interreligious dialogue and in the theology-and-science conversation comes together in this volume. The resulting Christianity-Buddhism-science trialogue opens up to new pneumatological perspectives on philosophical cosmology and anthropology in interdisciplinary and global context.
9.3 Method in Science and Religion: A Pneumatological AssistChapter Ten Spirit and Environment: Toward a Christian Ecological Ethic "After" Buddhism; 10.1 Pneumatological Theology and the Environment; 10.2 Buddhist Self-Emptying and the Environment; 10.3 Toward a Pneumato-ecological Ethic: Christian-Buddhist Convergences; Epilogue; Bibliography; Name Index; Subject Index
Description based upon print version of record.
Keywords: Buddhism -- Relations -- Christianity; Christianity and other religions -- Buddhism; Religion and science; Religion and science; Christianity and other religions -- Buddhism; Buddhism -- Relations -- Christianity; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books